Platinum-rhodium alloy powder for nitrogen-oxygen sensor electrode, preparation method of platinum-rhodium alloy powder and slurry for nitrogen-oxygen sensor electrode

Preparation of high alloyed platinum-rhodium electrode powder through chemical co-reduction and molten salt heat treatment, solving the problem of insufficient catalytic performance of platinum-rhodium electrodes in the prior art, improving the detection accuracy and reliability of nitrogen oxygen sensors, and realizing the low concentration of nitrogen Efficient detection of oxides.

CN119237757AActive Publication Date: 2025-01-03SUZHOU HONGPAI TECH CO LTD

Patent Information

Application Number
CN202411323383.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-03
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

The catalytic performance of the platinum-rhodium electrode in existing nitrogen oxygen sensors is poor in detection of low concentration nitrogen oxides, resulting in poor resolution and weak synergistic catalytic performance, making it difficult to accurately detect nitrogen oxides in automobile exhausts.

Method used

Platinum-rhodium alloy powder is prepared by combining chemical co-reduction and molten salt heat treatment to improve its alloying degree and particle density, enhance the uniformity of the three-phase interface of the catalytic functional phase and the zirconia electrolyte, thereby optimizing the catalytic efficiency and improving the electrode fluidity and compactness.

Benefits of technology

The catalytic capacity and response speed of the nitrogen oxide sensor electrode are significantly improved, the easy disconnection problem during the sintering process is reduced, the reliability and qualification rate of the sensor are improved, and the accurate detection of nitrogen oxide concentration is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119237757A_ABST
    Figure CN119237757A_ABST
Patent Text Reader

Abstract

The invention provides platinum-rhodium alloy powder for a nitrogen-oxygen sensor electrode, a preparation method of the platinum-rhodium alloy powder and slurry for the nitrogen-oxygen sensor electrode, and the preparation method of the platinum-rhodium alloy powder for the nitrogen-oxygen sensor electrode comprises the following steps: performing chemical co-reduction on a platinum metal precursor and a rhodium metal precursor to obtain composite powder, the particle size range of the composite powder is 50-100 nm; and carrying out molten salt heat treatment on the composite powder to obtain the submicron platinum-rhodium alloy powder for the nitrogen-oxygen sensor electrode. According to the platinum-rhodium alloy powder prepared through the method, the three-phase interface uniformity of a metal catalytic functional phase and a zirconium oxide ion electrolyte substrate in electrode slurry is improved, the catalytic capacity of an electrode is improved, meanwhile, the particle size of platinum-rhodium alloy particles is properly increased, and therefore the prepared electrode slurry has better flowability, and the service life of the electrode slurry is prolonged. The problem of easy wire breakage in the subsequent sintering process is reduced, and the yield and aging life of the sensor are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nitrogen oxygen sensors, and in particular to a platinum-rhodium alloy powder for nitrogen oxygen sensor electrodes, a preparation method thereof, and a slurry for nitrogen oxygen sensor electrodes. Background Art

[0002] The chip-type nitrogen oxide sensor is a kind of sensor used to detect nitrogen oxides (NO x ) content, which is usually composed of a zirconium oxide (ZrO2) matrix and nitrogen oxide sensitive electrode materials. The nitrogen oxide sensor separates nitrogen oxides from the exhaust gas through electrode catalytic reaction, and converts the measurement of nitrogen oxides into the measurement of O2 decomposed by nitrogen oxides. The sensor chip has two working chambers. The first chamber has an oxygen pump electrode. By applying a certain voltage to the oxygen pump, oxygen in the exhaust gas is first removed and the decomposition of nitrogen oxides is avoided; the second chamber reduces nitrogen oxides in the exhaust gas to N2 and O2 through a reducing agent, and then calculates the content of nitrogen oxides by detecting the oxygen concentration produced by the decomposition.

[0003] Platinum-rhodium electrodes are used as catalytic electrodes to accelerate the decomposition of nitrogen oxides in nitrogen oxide sensors, and play a decisive role in the response speed and sensitivity of the sensor. Therefore, the performance of platinum-rhodium electrodes is one of the most critical factors in determining the performance of nitrogen oxide sensors. In the prior art, mixed powders of platinum and rhodium are mainly used as the functional phase of catalytic electrodes. In such catalytic electrodes, the two metals of platinum and rhodium are in a submicron-level separated contact state, and the catalytic effect on low-concentration nitrogen oxides is poor. However, the concentration of nitrogen oxides in existing automobile exhaust is generally below 2000ppm, so the electrodes prepared from the above mixed powders show weak synergistic catalytic performance and poor resolution in application.

[0004] Therefore, it is necessary to design a platinum-rhodium alloy powder for nitrogen oxide sensor electrodes and a preparation method thereof and a slurry for nitrogen oxide sensor electrodes to solve the above problems. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing platinum-rhodium alloy powder for nitrogen oxygen sensor electrodes. The platinum-rhodium alloy powder prepared by the method has good dispersibility and high alloying degree, increases the uniformity of the three-phase interface of the metal catalytic functional phase and the zirconium oxide electrolyte substrate in the electrode, and improves the catalytic ability of the electrode; at the same time, the method increases the particle size and particle size uniformity of the platinum-rhodium alloy particles, so that the electrode slurry prepared by the method has better fluidity and density, and reduces the problem of easy disconnection in the subsequent sintering process.

[0006] To achieve the above object, the present invention adopts the following technical scheme: a method for preparing platinum-rhodium alloy powder for nitrogen oxygen sensor electrodes, comprising:

[0007] A platinum metal precursor and a rhodium metal precursor are subjected to a chemical co-reduction step to obtain a composite powder, wherein the composite powder comprises a platinum element powder and a rhodium element powder, wherein the weight ratio of the platinum element powder to the rhodium element powder is 0.8-1.2, and the particle size of the composite powder is in the range of 50-100 nm;

[0008] The composite powder is subjected to a molten salt heat treatment step to obtain submicron platinum-rhodium alloy powder for nitrogen oxygen sensor electrodes, and the purity of the platinum-rhodium alloy powder for nitrogen oxygen sensor electrodes is ≥99%.

[0009] As a further improved technical solution of the present invention, the chemical co-reduction step comprises:

[0010] S1. Dissolving chloroplatinic acid and rhodium trichloride in a solvent to form a mixed solution, wherein the mass concentration of chloroplatinic acid is 1% to 5%, and the mass concentration of rhodium trichloride is 1% to 5%; adding a reducing agent to the mixed solution at room temperature, stirring the reaction for 5 to 30 minutes, washing and drying to obtain the composite powder.

[0011] As a further improved technical solution of the present invention, in step S1, the reducing agent is lithium aluminum hydride, lithium borohydride, sodium borohydride or potassium borohydride, the amount of the reducing agent added is 5 to 15 times the total weight of chloroplatinic acid and rhodium trichloride, the reducing agent is added in the form of a solution, and the solution concentration of the reducing agent is 0.5 to 2M.

[0012] As a further improved technical solution of the present invention, the molten salt heat treatment step comprises:

[0013] S2, adding an inorganic mixed salt and a solvent to the composite powder until the inorganic mixed salt is completely dissolved, stirring evenly and heating to evaporate the solvent until the inorganic mixed salt crystals are precipitated;

[0014] S3. Put the material obtained in S2 into a furnace for heating and melting treatment, and then cool, wash and dry to obtain platinum-rhodium alloy powder.

[0015] As a further improved technical solution of the present invention, in step S2, the solvent is water or a volatile polar organic solvent, the inorganic mixed salt is a mixture of one or more of metal halides, nitrates, and sulfates, the metal is an alkali metal or an alkaline earth metal, the melting point of the inorganic mixed salt is 130 to 300°C, and the working temperature of the inorganic mixed salt is 400 to 700°C.

[0016] As a further improved technical solution of the present invention, in step S2, the inorganic mixed salt is sodium nitrate-potassium nitrate, calcium chloride-potassium chloride, potassium nitrate-sodium nitrite-sodium nitrate or sodium chloride-potassium chloride-calcium chloride; in step S3, the material heating rate is 0.5-1°C / s, the heat treatment temperature is 450-550°C, and the heat treatment time is 2-4h.

[0017] As a further improved technical solution of the present invention, it also includes:

[0018] S4. Mix the platinum-rhodium alloy powder obtained in S3 with water and zirconium oxide balls, and then perform ball milling, washing and drying to obtain a finished platinum-rhodium alloy powder; wherein the amount of water added is 3 to 10 times the total weight of the platinum-rhodium alloy powder, the amount of the zirconium oxide balls added is 2 to 5 times the total weight of the platinum-rhodium alloy powder, the particle size of the zirconium oxide balls is 0.5 to 1.0 mm, and the ball milling time is 20 to 30 hours.

[0019] As a further improved technical solution of the present invention, a surfactant is added during the ball milling process, and the amount of the surfactant added is 0.5% to 1% of the total weight of the platinum-rhodium alloy powder.

[0020] The present invention also aims to provide a platinum-rhodium alloy powder for nitrogen oxide sensor electrodes, which has a high degree of alloying, increases the three-phase interface bonding of the metal catalytic functional phase and the zirconium oxide ion electrolyte, and improves the catalytic ability of the electrode.

[0021] To achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a platinum-rhodium alloy powder for nitrogen oxygen sensor electrodes, which is prepared by any of the preparation methods described above, the particle shape of the platinum-rhodium alloy powder is spherical or nearly spherical, the particle size range is 0.8 to 1.2 μm, and the weight ratio of platinum element to rhodium element in the platinum-rhodium alloy powder is 1:(0.5 to 2).

[0022] The present invention also aims to provide a slurry for nitrogen oxide sensor electrodes, which has a high degree of alloying, increases the three-phase interface bonding of the metal catalytic functional phase and the zirconium oxide ion electrolyte, and improves the catalytic ability of the electrode.

[0023] To achieve the above object, the present invention adopts the following technical solution: a slurry for nitrogen oxygen sensor electrode, comprising the above-mentioned platinum-rhodium alloy powder for nitrogen oxygen sensor electrode. The preparation method of the electrode slurry is as follows:

[0024] The following raw materials are mixed according to the following weight percentages: 0.2wt%-1wt% of an inorganic binder phase, 10wt%-20wt% of an organic binder carrier, 50wt%-70wt% of a platinum-rhodium alloy powder, and 5wt%-10wt% of a zirconium oxide powder; wherein the platinum-rhodium alloy powder is a catalytic functional phase, and its particle size distribution is 0.8-1.2μm, its loose density is 2.3g / cm3, and its particle shape is spherical or nearly spherical; the zirconium oxide powder is zirconium oxide doped with 5% mol yttrium oxide (5YSZ), with a particle size of 300nm and a specific surface area of ​​2.4m 2 / g; the weight of the organic resin in the organic binder carrier is 5% to 10%, and the rest is an organic solvent. The organic resin is ethyl cellulose and / or acrylic resin, and the organic solvent is a mixture of one or more of pine alcohol, turpentine, butyl carbitol, and dibutyl phthalate; the inorganic binder phase is preferably alumina or silica.

[0025] Compared with the prior art, the present invention has the following advantages:

[0026] 1. The present invention combines chemical co-reduction with molten salt heat treatment to greatly improve the alloying degree of platinum-rhodium alloy powder (≥99%). Compared with the mixed powder of platinum nanopowder and rhodium nanopowder, the particles after high alloying of platinum and rhodium are atomically uniform and there is no positional difference of catalytic points. Therefore, the four-phase interface of traditional platinum particles, rhodium particles, zirconium oxide and gas is reduced to the three-phase interface of platinum-rhodium alloy particles, zirconium oxide and gas, thereby optimizing the synergistic catalytic efficiency of platinum and rhodium and improving the catalytic ability of the electrode.

[0027] 2. The present invention also further improves the particle density and particle size uniformity of the platinum-rhodium alloy, so that the prepared electrode slurry has better fluidity, thereby improving the density of the sintered electrode, thereby reducing the problem of easy wire breakage during sintering and improving the qualification rate and reliability of the nitrogen oxygen sensor chip.

[0028] 3. Compared with the traditional solid phase heat treatment, the molten salt in the present invention does not participate in the reaction, but only serves as a reaction medium. During the reaction, the formation of the molten salt fluid enhances the fluidity of the reaction components and significantly increases the diffusion rate, so the reaction temperature is significantly reduced and the reaction time is greatly shortened; the heat transfer of the molten salt method relies on liquid molten salt. Since the molten salt runs through the generated alloy powder particles, the surface energy and interface energy difference between the powder particles and the interior are regulated by the selection and proportion of the molten salt type, which effectively prevents the transition agglomeration and bonding between the composite particles, and avoids the abnormal growth of the particles due to direct close contact during the solid phase heat treatment process. Therefore, it is also easier to control the shape and size of the powder particles; at the same time, due to the solid-liquid interfacial tension effect, alloy particles that are approximately spherical can be obtained. Therefore, the molten salt heat treatment can obtain platinum-rhodium alloy powder with a more regular morphology and a more uniform particle size, so that the electronic slurry prepared from the platinum-rhodium alloy powder has a uniform three-phase interface after sintering, and the catalytic active points are uniform and controllable, so that the catalytic electrode is stable and controllable, and the zero-point potential is low. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is the X-ray diffraction pattern of the composite powder A in Example 1.

[0030] Figure 2 This is the X-ray diffraction pattern of the platinum-rhodium alloy powder A1 in Example 1.

[0031] Figure 3 This is a scanning electron microscope image of the composite powder A in Example 1.

[0032] Figure 4 This is a scanning electron microscope image of the platinum-rhodium alloy powder A1 in Example 1.

[0033] Figure 5 Test data of the catalytic electrode prepared with the platinum-rhodium electrode slurry B1 of Example 1 and applied to a nitrogen oxide sensor chip.

[0034] Figure 6 The catalytic electrode prepared with the platinum-rhodium electrode slurry B4 in Comparative Example 2 is used in the test data of the nitrogen oxide sensor chip. DETAILED DESCRIPTION

[0035] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0036] Example 1

[0037] Preparation of platinum-rhodium alloy powder A1 for nitrogen oxygen sensor electrodes:

[0038] Step 1: weigh 20g of chloroplatinic acid and 22g of rhodium trichloride in a beaker, add 100ml of deionized water to dissolve into a mixed solution; drip sodium borohydride solution into the mixed solution at room temperature and continue stirring, the molar concentration of the sodium borohydride solution is 1M, the dripping amount is 500ml, the dripping speed is 3ml / min, and the stirring reaction is continued for 10min after the sodium borohydride solution is dripped; after the chemical co-reduction reaction is completed, the product is washed and dried at a drying temperature of 60°C to obtain composite powder A; please refer to Figure 1 The XRD diagram of the composite powder A obtained in this embodiment is shown in FIG. 1 . The diffraction peaks of the composite powder A correspond to the standard cards PDF#05-0685 and PDF#04-0802 one by one. There are only the individual diffraction peaks of platinum and rhodium, indicating that the composite powder A includes platinum powder and rhodium powder. The weight ratio of platinum powder to rhodium powder in the composite powder A is 0.875. Please refer to Figure 3 , which is a scanning electron microscope image of the composite powder A obtained in step 1, it can be seen that the platinum and rhodium particles in the composite powder A are nanometer-sized. Specifically, the particle size range of the composite powder is 50-100 nm.

[0039] Step 2: Mix 75 grams of calcium chloride, 75 grams of potassium chloride solids and 200 grams of deionized water and stir to completely dissolve the solids to obtain an inorganic mixed salt solution; transfer 10 grams of composite powder A and the inorganic mixed salt solution to a porcelain crucible, stir evenly, and heat the mixture at 120° C. to gradually evaporate the water, and stop heating when a large amount of crystallization occurs; further, place the porcelain crucible in an oven and dry it at 110° C. until it no longer loses weight;

[0040] Step 3: putting the material obtained in step 2 into a molten salt heating furnace for heat treatment. Specifically, the molten salt heating furnace is heated to 500°C at a heating rate of 0.8°C / s and kept warm for 3 hours. During the heating and insulation process, the adjacent platinum and rhodium nanoparticles are gradually combined in the molten salt fluid and the alloying process is completed; then cooling, ultrasonically washing the heat-treated material with a large amount of deionized water for 5-10 times, and drying at 60°C;

[0041] Step 4: Mix the material obtained in step 3 with 5 times the weight of water, 3 times the weight of 1 mm diameter zirconium oxide balls, and 1% polyethylene glycol, transfer to a ball mill for ball milling dispersion, and ball milling for 24 hours at a speed of 250 rpm. Then wash with deionized water 3-5 times, and dry at 60°C to obtain highly dispersed platinum-rhodium alloy powder A1.

[0042] Please refer to Figure 2 The XRD diagram of the platinum-rhodium alloy powder A1 obtained in this embodiment is shown. It can be seen that the diffraction peaks of the platinum-rhodium alloy powder A1 correspond to the standard card PDF#27-0504 one by one, and there are no separate diffraction peaks of platinum and rhodium or other miscellaneous peaks, indicating that the platinum-rhodium alloy powder A1 has achieved a high degree of alloying, and the purity of the platinum-rhodium alloy powder is ≥99%, that is, the proportion of the alloy phase in the platinum-rhodium alloy powder is ≥99%. Please refer to Figure 4 The figure shows the SEM image of the platinum-rhodium alloy powder A1. It can be seen that the particle size of the platinum-rhodium alloy powder A1 can reach the submicron level. Specifically, the particle size of the platinum-rhodium alloy powder A1 is distributed in the range of 0.8 to 1.2 μm, and the bulk density is 2.3 g / cm 3 .

[0043] Further, platinum-rhodium alloy powder A1 was used to prepare platinum-rhodium electrode slurry B1:

[0044] The platinum-rhodium electrode slurry B1 is prepared from the following raw materials according to weight percentage: 80wt% of platinum-rhodium alloy powder A1, 5wt% of zirconium oxide, 0.5wt% of aluminum oxide, and 14.5wt% of an organic binder carrier. The zirconium oxide powder is zirconium oxide doped with 5% mol yttria (5YSZ), with a particle size of 300nm and a specific surface area of ​​2.4m 2 / g; in other embodiments, the inorganic binder phase may also be selected from inorganic powders such as silicon dioxide and talcum powder; the organic binder is a mixture of an organic resin and an organic solvent, wherein the organic resin content is 8% and the rest is an organic solvent, the organic resin is ethyl cellulose, and the organic solvent is pinene alcohol. The above components are mixed and ground on a three-roll grinder with a grinding fineness of 5 μm to obtain a platinum-rhodium electrode slurry B1.

[0045] Example 2

[0046] Preparation of platinum-rhodium alloy powder A2 for nitrogen oxygen sensor electrodes:

[0047] Step 1: The same as in Example 1, to obtain composite powder A;

[0048] Step 2: Mix 75 grams of sodium nitrate and 75 grams of potassium nitrate solids with 200 grams of deionized water and stir until the solids are completely dissolved to obtain an inorganic mixed salt solution; transfer 10 grams of composite powder A and the inorganic mixed salt solution to a porcelain crucible, stir evenly, and heat the mixture at 120° C. to gradually evaporate the water, and stop heating when a large amount of crystallization occurs; further, place the porcelain crucible in an oven and dry it at 110° C. until it no longer loses weight;

[0049] Step 3: placing the material obtained in step 2 into a molten salt heating furnace for heat treatment. Specifically, the molten salt heating furnace is heated to 550°C at a heating rate of 1.0°C / s, and kept warm for 2.5 hours, and then cooled. The heat-treated material is ultrasonically washed 5-10 times with a large amount of deionized water, and dried at 60°C to obtain a platinum-rhodium alloy powder.

[0050] Step 4: Consistent with Example 1, highly dispersed platinum-rhodium alloy powder A2 is obtained.

[0051] The diffraction peaks of the XRD pattern of the platinum-rhodium alloy powder A2 obtained in this example correspond to the standard card PDF#27-0504 one by one, and there are no separate diffraction peaks of platinum and rhodium or other miscellaneous peaks, and the platinum-rhodium alloy powder A2 is also submicron-grade. The purity of the platinum-rhodium alloy powder A2 is ≥99%.

[0052] Furthermore, platinum-rhodium alloy powder A2 is used to prepare platinum-rhodium electrode slurry B2: the same as in Example 1, to obtain platinum-rhodium electrode slurry B2.

[0053] Comparative Example 1

[0054] Preparation of platinum-rhodium composite powder A3:

[0055] Step 1: Mix 75 grams of calcium chloride and 75 grams of potassium chloride solids with 200 grams of deionized water and stir to completely dissolve the solids to obtain an inorganic mixed salt solution; transfer a total of 10 grams of nano-platinum powder and nano-rhodium powder and the inorganic mixed salt solution to a porcelain crucible, stir evenly, and heat the mixture at 120°C to gradually evaporate the water, and stop heating when a large amount of crystallization occurs; further, put the porcelain crucible into an oven and dry it at 110°C until it no longer loses weight; wherein, nano-platinum powder and nano-rhodium powder are both commercially available, and their particle size range is 50 to 100 nm, and the nano-platinum powder and nano-rhodium powder are added in an equal weight ratio.

[0056] Step 3: Place the product obtained in step 2 into a molten salt heating furnace, heat it to 500°C at a heating rate of 0.8°C / s, and keep it warm for 3 hours, then cool it, ultrasonically wash it with a large amount of deionized water for 5-10 times, and dry it at 60°C;

[0057] Step 4: Mix the material obtained in step 3 with 5 times water, 3 times 1 mm diameter zirconium oxide balls, and 1% polyethylene glycol, transfer to a ball mill for ball milling dispersion, and ball milling time at 250 rpm for 24 hours, then wash with deionized water 3-5 times, and obtain highly dispersed platinum-rhodium composite powder A3 after drying.

[0058] Further, a platinum-rhodium electrode slurry B3 is prepared: the preparation method is generally consistent with that in Example 1, except that the platinum-rhodium alloy powder A1 in Example 1 is replaced by a platinum-rhodium composite powder A3 to prepare a platinum-rhodium electrode slurry B3.

[0059] Comparative Example 2

[0060] Preparation of platinum-rhodium composite powder A4:

[0061] Step 1: The same as in Example 1, to obtain composite powder A;

[0062] Step 2: The same as in Example 1;

[0063] Step 3: Place the material obtained in step 2 into a molten salt heating furnace for heat treatment. Specifically, the molten salt heating furnace is heated to 850°C at a heating rate of 0.8°C / s and kept warm for 3 hours, then cooled, and the heat-treated material is ultrasonically washed 5-10 times with a large amount of deionized water and dried at 60°C;

[0064] Step 4: Consistent with Example 1, obtain platinum-rhodium composite powder A4.

[0065] Further, a platinum-rhodium electrode slurry B3 is prepared: the preparation method is generally consistent with that in Example 1, except that the platinum-rhodium alloy powder A1 in Example 1 is replaced by a platinum-rhodium composite powder A4 to prepare a platinum-rhodium electrode slurry B4.

[0066] Comparative Example 3

[0067] Preparation of platinum-rhodium electrode slurry B5: The preparation method is generally the same as that in Example 1, except that 80 wt% of the platinum-rhodium alloy powder A1 in Example 1 is replaced with a mixed powder of 40 wt% nano-platinum powder and 40 wt% nano-rhodium powder to obtain platinum-rhodium electrode slurry B4.

[0068] The performance tests were performed on the platinum-rhodium electrode slurries of Examples 1, 2 and Comparative Examples 1, 2 and 3:

[0069] Viscosity test: The viscosity of platinum-rhodium electrode slurries B1, B2, B3, B4 and B5 was measured at 25°C using a Broodfield #52 / 1.5 rpm viscometer.

[0070] Platinum-rhodium electrode slurries B1, B2, B3, B4 and B5 were printed on the zirconia green ceramic film substrate with a pattern of 10 cm long and 0.1 cm wide lines, and then sintered at 1500°C for 2 hours. After sintering, the resistance was tested with a multimeter. Please refer to Table 2 for the above test results.

[0071] Table 2 Performance parameter test table of platinum-rhodium electrode slurry B1, B2, B3, B4 and B5

[0072] B1 B2 B3 B4 B5 Slurry viscosity (Pa·s) 198 195 204 212 200 Resistivity (Ω·cm) <![CDATA[2.2×10 -4 ]]> <![CDATA[2.3×10 -4 ]]> <![CDATA[2.8×10 -4 ]]> <![CDATA[3.4×10 -4 ]]> <![CDATA[3.3×10 -4 ]]>

[0073] The sintered electrodes of 10 platinum-rhodium electrode pastes B1 and B2 obtained in Example 1 and Example 2 were measured, and the electrical conductivity was 100%, and the resistivity was as low as 2.2×10 -4 Ω·cm; 10 electrodes sintered with the platinum-rhodium electrode slurry B4 obtained in Comparative Example 3 were measured, and the conductivity was 30% and the resistivity was 3.4×10 -4 Ω·cm, indicating that the electrode slurry of Comparative Example 3 has the risk of easy disconnection in the application of preparing electrodes. The electrical conductivity and resistivity of 10 electrodes sintered from the platinum-rhodium electrode slurries B3 and B5 were measured to be between B1 and B4.

[0074] In addition, the present invention applies the catalytic electrodes prepared by the platinum-rhodium electrode slurries B1, B2, B3, B4 and B5 to the nitrogen oxide sensor chip. Figure 5 and Figure 6 The test data of B1 and B4 are shown in Figure 1, where the horizontal axis is time (s) and the vertical axis is current (nA). The larger the vertical axis peak value, the higher the electrode activity. From the chip test data, it can be seen that the chip current of the chip made of platinum-rhodium electrode slurry B4 in air is about 180nA, and in NO atmosphere, the chip IP2 (NO x The actual concentration of the sensor limiting current reflects the sensor's NO x The response limit of concentration change is 915nA; in addition, the IP2 of the chips prepared with the slurries in other comparative examples are all lower than 1000nA; while the current in the air of the chip made of the platinum-rhodium electrode slurry B1 of the present invention is close to zero, and under the same concentration of NO atmosphere, the IP2 of the chip reaches 3100nA, and the electrode catalytic activity is greatly improved, which can ensure that the sensor can accurately monitor and control the nitrogen oxide content in automobile exhaust.

[0075] The above embodiments are only used to illustrate the present invention but not to limit the technical solutions described in the present invention. The understanding of this specification should be based on the technicians in the relevant technical field. Although this specification has described the present invention in detail with reference to the above embodiments, ordinary technicians in the field should understand that technicians in the relevant technical field can still modify or replace the present invention with equivalents, and all technical solutions and improvements that do not depart from the spirit and scope of the present invention should be covered within the scope of the claims of the present invention.

Claims

1. A method for preparing platinum-rhodium alloy powder for nitrogen oxygen sensor electrodes, characterized in that: include: A platinum metal precursor and a rhodium metal precursor are subjected to a chemical co-reduction step to obtain a composite powder, wherein the composite powder comprises a platinum element powder and a rhodium element powder, wherein the weight ratio of the platinum element powder to the rhodium element powder is 0.8-1.2, and the particle size of the composite powder is in the range of 50-100 nm; The composite powder is subjected to a molten salt heat treatment step to obtain submicron platinum-rhodium alloy powder for nitrogen oxygen sensor electrodes, and the purity of the platinum-rhodium alloy powder for nitrogen oxygen sensor electrodes is ≥99%.

2. The method for preparing platinum-rhodium alloy powder for nitrogen oxygen sensor electrodes according to claim 1, characterized in that: The chemical co-reduction step comprises: S1. Dissolving chloroplatinic acid and rhodium trichloride in a solvent to form a mixed solution, wherein the mass concentration of chloroplatinic acid is 1% to 5%, and the mass concentration of rhodium trichloride is 1% to 5%; adding a reducing agent to the mixed solution at room temperature, stirring the reaction for 5 to 30 minutes, washing and drying to obtain the composite powder.

3. The method for preparing platinum-rhodium alloy powder for nitrogen oxygen sensor electrodes according to claim 2, characterized in that: In step S1, the reducing agent is lithium aluminum hydride, lithium borohydride, sodium borohydride or potassium borohydride, and the amount of the reducing agent added is 5 to 15 times the total weight of chloroplatinic acid and rhodium trichloride. The reducing agent is added in the form of a solution, and the solution concentration of the reducing agent is 0.5 to 2M.

4. The method for preparing platinum-rhodium alloy powder for nitrogen oxygen sensor electrode according to claim 1, characterized in that: The molten salt heat treatment step comprises: S2, adding an inorganic mixed salt and a solvent to the composite powder until the inorganic mixed salt is completely dissolved, stirring evenly and heating to evaporate the solvent until the inorganic mixed salt crystals are precipitated; S3. Put the material obtained in S2 into a furnace for heating and melting treatment, and then cool, wash and dry to obtain platinum-rhodium alloy powder.

5. The method for preparing platinum-rhodium alloy powder for nitrogen oxygen sensor electrode according to claim 4, characterized in that: In step S2, the solvent is water or a volatile polar organic solvent, the inorganic mixed salt is a mixture of one or more of metal halides, nitrates, and sulfates, the metal is an alkali metal or an alkaline earth metal, the melting point of the inorganic mixed salt is 130 to 300° C., and the working temperature of the inorganic mixed salt is 400 to 700° C.

6. The method for preparing platinum-rhodium alloy powder for nitrogen oxygen sensor electrodes according to claim 4, characterized in that: In step S2, the inorganic mixed salt is sodium nitrate-potassium nitrate, calcium chloride-potassium chloride, potassium nitrate-sodium nitrite-sodium nitrate or sodium chloride-potassium chloride-calcium chloride; in step S3, the material heating rate is 0.5-1°C / s, the heat treatment temperature is 450-550°C, and the heat treatment time is 2-4h.

7. The method for preparing platinum-rhodium alloy powder for nitrogen oxygen sensor electrodes according to claim 4, characterized in that: Also includes: S4. Mix the platinum-rhodium alloy powder obtained in S3 with water and zirconium oxide balls, and then perform ball milling, washing and drying to obtain a finished platinum-rhodium alloy powder; wherein the amount of water added is 3 to 10 times the total weight of the platinum-rhodium alloy powder, the amount of the zirconium oxide balls added is 2 to 5 times the total weight of the platinum-rhodium alloy powder, the particle size of the zirconium oxide balls is 0.5 to 1.0 mm, and the ball milling time is 20 to 30 hours.

8. The method for preparing platinum-rhodium alloy powder for nitrogen oxygen sensor electrodes according to claim 7, characterized in that: A surfactant is added during the ball milling process, wherein the amount of the surfactant added is 0.5% to 1% of the total weight of the platinum-rhodium alloy powder.

9. A platinum-rhodium alloy powder for nitrogen oxygen sensor electrodes, characterized in that: The platinum-rhodium alloy powder for the nitrogen oxygen sensor electrode is prepared by the preparation method described in any one of claims 1 to 8, the particle shape of the platinum-rhodium alloy powder is spherical or nearly spherical, the particle size range is 0.8 to 1.2 μm, and the weight ratio of platinum element to rhodium element in the platinum-rhodium alloy powder is 1:(0.5 to 2).

10. A slurry for nitrogen oxygen sensor electrode, characterized in that: It comprises the platinum-rhodium alloy powder for nitrogen oxygen sensor electrodes as described in claim 9.

Citation Information

Patent Citations

  • Method for preparing precious metal nanoparticle

    CN101497133A

  • Method for preparing aluminum alloy powder through salt melting method

    CN104625081A

  • Nanoscale platinum-rhodium alloy powder and preparing method thereof

    CN106623975A

  • Platinum alloy catalyst, molten salt thermal preparation method and proton exchange membrane fuel cell

    CN110518265A

  • Shaping method of silicon carbide powder particles

    CN113264527A

Cited By

  • Platinum-based alloy slurry for aluminum oxide co-firing and heating electrode

    CN120356720A

  • A platinum-based alloy slurry for alumina co-firing and a heating electrode

    CN120356720B